2012
DOI: 10.4300/jgme-d-11-00284.1
|View full text |Cite
|
Sign up to set email alerts
|

System-Based Approach to Educating Internal Medicine Residents on Preventable Hospital Readmissions

Abstract: Background A literature gap exists in educating internal medicine residents about hospital readmissions and how to prevent them. Intervention The study aimed to implement a readmissions education initiative for general internal medicine inpatient resident teams in 3 general practice units at an urban, tertiary hospital. Methods Senior residents were given acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…In accordance with previous studies [15], all residents could verify their conclusions with a senior professional. The first month of this study was a pilot phase to evaluate the feasibility and reliability of the screening, interview and review process.…”
Section: Study Process and Data Collectionsupporting
confidence: 79%
See 1 more Smart Citation
“…In accordance with previous studies [15], all residents could verify their conclusions with a senior professional. The first month of this study was a pilot phase to evaluate the feasibility and reliability of the screening, interview and review process.…”
Section: Study Process and Data Collectionsupporting
confidence: 79%
“…Interdepartmental, integrated care issues and medication errors were recognized by the different members of the team. Previous studies using a multidisciplinary approach are limited [15,23,26,27] and, to our knowledge, none of them specifically described the added value of this approach. The multidisciplinary meeting resulted in a modification of the final conclusion on preventability in 1 in 9 cases.…”
Section: Plos Onementioning
confidence: 99%
“…Several studies used an existing tool, like the STate Action on Avoidable Rehospitalizations (STAAR) initiative [14, 21, 27, 30, 34] or root cause approach [5, 18, 24, 3537] but all others adapted an existing tool or developed their own tool based on previous publications. For the purpose of this article we focused only on the distinction between studies using an a priori preventability cause classification [1316, 19, 2126, 31, 35, 3755], or not [5, 17, 18, 20, 2730, 32, 33, 36, 5659], see Table 2 . As an example of an a priori cause classification, Clarke et al reported, Unavoidable causes: chronic or relapsing disorder; unavoidable complication, readmission for social or psychological reason, reasons probably beyond control of hospital services, completely different diagnosis from previous admission.…”
Section: Resultsmentioning
confidence: 99%
“…3,40 Driven by a consumer push toward a higher quality of care and programs such as the HRRP, there has been increasing interest and research in reducing readmissions, especially those identified as preventable. 4,19,27 By recent estimates, preventable readmissions make up as much as 20% of these cases and cost up to $17 billion annually. 37 There are also ongoing efforts to better understand and identify the factors that lead to readmission, which can lead to the development of more effective interventions.…”
mentioning
confidence: 99%